Evaluasi Gameplay Autochess Mobile Game Menggunakan Mechanic Dynamic Aesthetic Framework - Abdul Hakim; Eriq Muhammad Adams Jonemaro; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Game is one of the entertaiment thing which have many people inetersted of. Nowadays games has so many genre, for example card game, board game and Video game. For video game, there is so many platforms that you can play with, like Console, Pc Games and Mobile games. in mobile games, Auto Chess is one of strategy based genre which you can download on google play store. Based on google play rating, Auto Chess Mobile has the lowest score compared to the other games who have same genre, one of the lowest score is on gameplay. therefore, research is conducted on the gameplay of Auto Chess Mobile games with Mechanic Dynamic Aesthetic Framework. in this method, data collection is obtained by doing solo testing and playtesing with two particapnts who plays Auto Chess Mobile Game. based on the analysis that has been done by doing solo testing and playtesting with two particapants, obtained recommendations for doing enhancment and reduction for damage from the skill of some the heroes, enhancment and reduction from some of the synergy, enhancment and reduction of the base stat for some heroes and how to use the item for the heroes. recomendation result will be categories by Formal Elements Of Game